2021
DOI: 10.1021/acs.inorgchem.1c01218
|View full text |Cite
|
Sign up to set email alerts
|

Homochiral Ferromagnetic Coupling Dy2 Single-Molecule Magnets with Strong Magneto-Optical Faraday Effects at Room Temperature

Abstract: By the bridging action of the 6-chloro-2-hydroxypyridine (Hchp) ligand and the terminal coordination role of the homochiral ligand, (−)/(+)-3-trifluoroacetyl camphor (l-Htfc/d-Htfc), a pair of enantiomerically pure dysprosium­(III) dinuclear complexes, [Dy2(l-tfc)4(chp)2(MeOH)2] (l-1) and [Dy2(d-tfc)4(chp)2(MeOH)2] (d-1), was obtained. Their circular dichroism (CD) spectra verified their enantiomeric nature. Magnetic investigation indicated that they exhibit ferromagnetic interaction and good zero field single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 93 publications
2
59
0
Order By: Relevance
“…Description of the Structures. Single-crystal structure analysis indicated that R-1-Dy/S-1-Dy and R-2-Dy/S-2-Dy belong to homochiral enantiomeric pairs with near-zero Flack parameter values of 0.006(12)/0.008 (9) for R-1-Dy/S-1-Dy and −0.032(16)/0.018 (9) for R-2-Dy/S-2-Dy, and all of them crystallize in noncentrosymmetric monoclinic space group P2 1 . Thus, the structures of R-1-Dy and R-2-Dy as representatives are described in detail.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Description of the Structures. Single-crystal structure analysis indicated that R-1-Dy/S-1-Dy and R-2-Dy/S-2-Dy belong to homochiral enantiomeric pairs with near-zero Flack parameter values of 0.006(12)/0.008 (9) for R-1-Dy/S-1-Dy and −0.032(16)/0.018 (9) for R-2-Dy/S-2-Dy, and all of them crystallize in noncentrosymmetric monoclinic space group P2 1 . Thus, the structures of R-1-Dy and R-2-Dy as representatives are described in detail.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Multifunctional coordination compounds (CCs) have been the hot subject of research in the fields of coordination chemistry and materials science, , and the use of homochiral ligands is an effective approach to prepare multifunctional CCs that possess unique physical properties, such as second-harmonic generation (SHG), ferroelectricity, piezoelectricity, and pyroelectricity, which are only related to the lack of an inversion center. In particular, introducing chirality into magnetic CCs, the resulting chiral CCs may exhibit enchanting magnetochiral dichroism, a magneto-optical Faraday effect, and a magnetoelectric coupling phenomenon, being expected to be able to furnish the original solutions in high-density data storage and quantum computing. In terms of magnetism, lanthanide ions (Ln III ), especially the Dy III ion, have large spin ground state and magnetic anisotropy, making them suitable for constructing high-performance single-molecule/ion magnets (SMMs/SIMs) that have promising applications in information storage, quantum computing, and molecular spintronics. Among the reported Dy III SMMs/SIMs, mononuclear species with high D 4 d , D 5 h , D 6 h , C ∞ v , and D ∞ h axial symmetries have been shown to be ideal candidates for exhibiting high-performance SIM behavior. However, the mononuclear chiral Dy III SIMs among them are rather scarce, mainly due to the difficulty of controlling chirality in the whole magnetic molecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if chirality is introduced into molecular magnets, it will bring valuable physical properties such as nonlinear optics, ferroelectricity, and magneto-optical effects, making them attractive multifunctional molecular materials. The general case is to obtain chiral structured molecule-based magnets by chiral ligand coordination or even by cocrystallizing with chiral organic molecules .…”
Section: Introductionmentioning
confidence: 99%
“…In high-temperature regions, the χ M T products of 1 , 2 , and 3 decrease slowly and reach the respective minimum values of 23.08 ( 1 , 9.0 K), 11.65 ( 2 , 2.0 K), and 6.81 ( 3 , 2.0 K) cm 3 K mol −1 , usually caused by antiferromagnetic couplings between adjacent lanthanide (III) ions, and/or depopulation of Ln 3+ ions excited Stark (M J ) sublevels ( Lim et al, 2016 ; Liu et al, 2016 ; Li J et al, 2021 ). Upon lowering the temperature to 2.0 K, the χ M T value of 1 rises again to a maximum of 24.40 cm 3 K mol −1 , indicating the existence of weak intramolecular ferromagnetic interactions between the paramagnetic dysprosium (III) centers ( Gao et al, 2019 ; Shen et al, 2020 ; Li X et al, 2021 ; Liu et al, 2021 ). In 4 , the χ M T values are almost unchanged from 300 to 30.0 K and drop eventually to around 2.0 K to 12.64 cm 3 K mol −1 , suggesting the occurrence of antiferromagnetic Gd 3+ ∙∙∙Gd 3+ coupling.…”
Section: Resultsmentioning
confidence: 99%